Anthropocentrism and solipsism in photographic self-portraits of Edvard Munch. (4th May 2022) - Peraica, Ana
Abstract : Although mental illnesses and personality disorders are largely destigmatized in the contemporary age, some genres, such as self-portraiture and consequently selfies, are still framed in interpretation by diagnostic labeling. One of the disorders that was often taken into reference when approaching self-picturing is narcissism. However, such an approach to the visual genre is limiting its interpretation. This article analyses two sets of self-portrait photographs of a Norwegian painter Edvard Munch, who spent some time in psychiatric asylums. This episode divides his work into two phases. In the first period, Munch self-records his various actions in space, while in the second one, he focuses on his face and a static half-a-figure. While the first one is actively reinterpreting the world through the self-image, the second one is centering the self as the world itself. Rather than defining which sets are more narcissistic, this article proposes distinguishing between performative/extravert and contemplative/introvert definitions of self-pictures by defining anthropocentric and solipsistic self-portraits. Distinguishing between anthropocentric and solipsistic self-portraiture may have impact not only on analysis of Munch's photographic and painterly self-portraits but also on the interpretation of contemporary genre of selfies as well.